PENGARUH KEBIJAKAN INFLATION TARGETING FRAMEWORK (ITF) DALAM MEMODERASI VARIABEL MONETER TERHADAP INFLASI DI INDONESIA - Ratih Ratna Sari; Yeniwati Yeniwati (Universitas Negeri Padang, 2019)
This study aims to determine the effect of the inflation targeting framework (ITF) policy or the inflation target in moderating monetary variables to inflation in Indonesia. The data used are secondary data in the form of time series from 2005: Q3 to 2018: Q4, with documentation data collection techniques and library studies obtained from relevant institutions and agencies. The variables used are interest rates (X1), the money supply (X2), and exchange rates (X3) as independent variables. Variable inflation targeting framework or inflation target (X4) as a moderating and inflation variable (Y) as the dependent variable. The research method used is Moderated Regression Analysis (MRA). The results of the study show that (1) Partially interest rate and money supply significant positive effect to inflation in Indonesia. (2) Partilally exchange rate and inflation target do not have a signifivant effect to inflation in Indonesia. (3)Partially the inflation target is able to moderate interest rates to inflation in Indonesia. The inflation target is pure moderation. (4) Partially the inflation target is not able to moderate the money supply to inflation, where the inflation target is only a potential moderating variable. (5) Partially the inflation target is not able to moderate the exchange rate to inflation, where the inflation target is only a potential moderating variable